Influence of blue village to interest in entrepreneurship - Yunita, Reni Dwi; Windarani, Novia Ayu (Journal of Social Studies, 2018)
Many places that are currently used as tourist attractions, especially on the renewal of the town. One of them is Blue Village located in Embong Brantas RW 04 and RW 05 District Kidul Dalem. From the potential of tourism is expected to increase the creativity and employment of new citizens of embong brantas able to develop to advance the welfare of life and creativity in the field of entrepreneurship. This research uses quantitative method. Data analysis using t-test and crosstabs. The results show that blue village affects entrepreneurship interest with a significance level of < 0.5. Interest in entrepreneurship is supported by factors of ability, willingness, motivation, support, innovation and creativity. Respondents with a productive age will be very potential in developing entrepreneurial interests.